Deadpool. 3, The good, the bad and the ugly - Duggan, Gerry; Koblish, Scott; Liefeld, Rob.; Nicieza, Fabian; Posehn, Brian, 1966-; Shalvey, Declan (New York, NY : Marvel Worldwide, Inc., a subsidiary of Marvel Entertainment, LLC, 2013)
When Deadpool's past as a hero-for-hire with Power Man and Iron Fist during the 1970s returns to haunt him, Deadpool must track down his "old friends" for a rematch. Then, the "Merc with a Mouth" enlists the relucant help of Wolverine and Captain America when his past in the Weapon X Program is weaponized.
"Collected Editions"--Inside front cover.
"Contains material originally published in magazine form as Deadpool #13-19"--T.p.
"Deadpool created by Rob Liefeld and Fabian Nicieza"--T.p. verso.
"Parental advisory"--Back cover.
Adult
Adult
Keywords: Assassins -- Comic books, strips, etc. -- Fiction; Deadpool (Fictitious character) -- Comic books, strips, etc. -- Fiction; Good and evil -- Comic books, strips, etc. -- Fiction; Superheroes -- Comic books, strips, etc. -- Fiction; Assassins -- Comic books, strips, etc. -- Fiction; Comic books, strips, etc; Deadpool (Fictional character) -- Comic books, strips, etc. -- Fiction; Good and evil -- Comic books, strips, etc. -- Fiction; Graphic novels; Superhero graphic novels; Superheroes -- Comic books, strips, etc. -- Fiction; Graphic novels; Superhero comic books, strips, etc